First, simplify the equation so the absolute value is all that remains on the left side of the equation:
|2x – 25| = 10
Now create two equalities, one for 10 and one for –10.
You are watching: Which of the following is a solution?
2x – 25 = 10 and 2x – 25 = –10
2x = 35 and 2x = 15
x = 17.5 and x = 7.5
The two solutions are 7.5 and 17.5. 17.5 + 7.5 = 25
When you divide a number by 3 and then add 2, the result is the same as when you multiply the same number by 2 then subtract 23. What is the number?
You set up the equation and you get: (x/3) + 2 = 2x – 23.
Add 23 to both sides: (x/3) + 25 = 2x
Multiply both sides by 3: x + 75 = 6x
Subtract x from both sides: 75 = 5x
Divide by 5 and get x = 15
First, we need to get everything on one side so that the equation equals zero.
2x2 - 2x -2 = 1-x
We need to add x to the left, and then subtract 1.
2x2 - 2x -2 +x - 1 = 0
2x2 - x - 3 = 0
Now we need to factor the binomial. In order to do this, we need to multiply the outer two coefficients, which will give us 2(-3) = -6. We need to find two numbers that will mutiply to give us -6. We also need these two numers to equal -1 when we add them, because -1 is the coefficient of the x term.
If we use +2 and -3, then these two numbers will multiply to give us -6 and add to give us -1. Now we can rewrite the equation as follows:
2x2 - x - 3 = 2x2 + 2x - 3x - 3 = 0
2x2 + 2x - 3x - 3 = 0
Now we can group the first two terms and the last two terms. We can then factor the first two terms and the last two terms.
See more: Is Duff Goldman Single - Who Is Duff Goldman Dating
2x(x+1) -3(x+1) = 0
(2x-3)(x+1) = 0
This means that either 2x - 3 = 0, or x + 1 = 0. So the values of x that solve the equation are 3/2 and -1.
The question asks us for the sum of the solutions, so we must add 3/2 and -1, which would give us 1/2.